Plugging compositions and materials and their use

CN119677825BActive Publication Date: 2026-10-16CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380054862.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-09-06
Filing Date
2023-08-24
Publication Date
2026-10-16
Estimated Expiration
2043-08-24

AI Technical Summary

Technical Problem

[0007]本发明的目的是为了克服现有技术存在的堵漏组合物在抗冲稀、抗高温以及抗压强度等方面表现不佳的问题,提供堵漏组合物和堵漏材料及其应用,该堵漏组合物适合应用于含流动水的地层

Benefits of technology

[0014] (1) The plugging composition of the present invention can cross-link to form a gel before or during injection into the formation. The gel can solidify at the lost formation to form a plugging material. The mass retention rate of the gel is above 90% when flushed with water at a flow rate of 10 m/min for 30 min at 50-180°C. After injection into the water-bearing formation, it can strongly reside around the wellbore and solidify under formation conditions to generate a plugging material with an overlap shear strength of 0.1-0.14 MPa and a compressive strength of not less than 16 MPa, ultimately plugging the lost formation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure QLYQS_3
    Figure QLYQS_3
Patent Text Reader

Abstract

The present application relates to the field of oil drilling, and discloses a plugging composition and plugging material and application thereof. The plugging composition can cross-link to form a gel before or during injection into a formation, and the gel can solidify to form a plugging material at a lost circulation zone, wherein the mass retention rate of the gel is above 90% under the condition of 50-180 DEG C and water flow speed of 10 m / min for 30 min; and the lap shear strength of the plugging material is 0.1-0.14 MPa. The plugging composition of the present application is suitable for water-bearing formations with temperature not higher than 180 DEG C, especially formations containing flowing water. The plugging composition of the present application can cross-link to form a gel, and after injection into a water-bearing formation, it can strongly stay around a wellbore and solidify to form a plugging material under formation conditions, finally plugging the lost circulation zone. The plugging material of the present application has significant improvement in water dilution resistance, interfacial bonding strength and high temperature resistance.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Cross-reference to related applications

[0002] This application claims the benefit of Chinese patent applications 202211082422.9, 202211082409.3 and 202211082427.1, filed on September 6, 2022, the contents of which are incorporated herein by reference. Technical Field

[0003] This invention relates to the field of oil drilling technology, and more specifically to plugging compositions and materials and their applications. Background Technology

[0004] Aquifers are usually connected to underground rivers, and the groundwater is very active. Well leaks are rapid and large in volume, making them difficult to handle. There is currently no particularly good method to plug leaks in aquifers, mainly because the plugging slurry is easily diluted or carried away by the water flow. The direct results are: (1) dilution reduces the viscosity of the plugging slurry and the concentration of the plugging material, making it easy to flow away under pressure and difficult to accumulate near the entrance of the leaking layer; (2) for solidified plugging slurry, dilution makes it difficult to solidify or greatly reduces the solidification strength, making it difficult to support the destructive effect of the mud, thus causing the plugging to fail; (3) if the formation water is flowing water, the plugging slurry will be quickly carried away by the formation water under the action of the water flow, failing to form a sealing wall and causing the plugging to fail. The plugging of aquifers, especially those with flowing water, has not been well solved.

[0005] CN111849437A relates to a pretreatment agent for plugging leaks in water-bearing formations in the field of oil drilling, its preparation method, and its application. The pretreatment agent for plugging leaks in water-bearing formations comprises the following components by weight: 100 parts water-soluble phenolic resin, 0.110 parts water-soluble phenolic emulsifier, and 10-400 parts water. However, this pretreatment agent only forms a highly adhesive substance with strong wall adhesion in water-bearing formations, and is easily washed away by water when applied to formations containing flowing water.

[0006] Therefore, there is an urgent need to develop a plugging composition suitable for formations containing flowing water that exhibits excellent performance in terms of erosion resistance, retention capacity, high temperature resistance, and compressive strength. Summary of the Invention

[0007] The purpose of this invention is to overcome the problems of poor performance of existing plugging compositions in terms of erosion resistance, high temperature resistance, and compressive strength, and to provide plugging compositions and plugging materials and their applications. The plugging composition is suitable for use in formations containing flowing water.

[0008] To achieve the above objectives, the first aspect of the present invention provides a plugging composition, wherein the plugging composition can crosslink to form a gel before or during injection into the formation, the gel can solidify at the site of the lost formation to form a plugging material, wherein the mass retention rate of the gel is above 90% after being flushed with water at a flow rate of 10 m / min for 30 min at 50-180°C; and the overlap shear strength of the plugging material is 0.1-0.14 MPa.

[0009] A second aspect of the present invention provides a sealing material, which is obtained by curing the aforementioned sealing composition.

[0010] A third aspect of the present invention provides the application of the aforementioned plugging composition or the aforementioned plugging material in oil well formation plugging; preferably, the oil well formation is a water-bearing oil well formation at 50-180°C.

[0011] A fourth aspect of the present invention provides a method for plugging leaks in oil wells. The method includes directly injecting the aforementioned plugging composition into formation fractures in the oil well, causing the plugging composition to cross-link and form a gel during the injection process; or injecting the aforementioned plugging composition into formation fractures after forming a gel, wherein, under formation conditions, the gel solidifies at the site of the leak to form a plugging material; wherein the gel retains more than 90% of its mass after being flushed with water at a flow rate of 10 m / min for 30 minutes at 50-180°C; and the overlap shear strength of the plugging material is 0.1-0.14 MPa.

[0012] The aforementioned plugging composition or the aforementioned plugging material is used in the process of leakage in formations containing flowing water; especially in the process of leakage in formations containing flowing water at temperatures of 50-180°C.

[0013] The beneficial technical effects achieved by the present invention through the above technical solution are as follows:

[0014] (1) The plugging composition of the present invention can cross-link to form a gel before or during injection into the formation. The gel can solidify at the lost formation to form a plugging material. The mass retention rate of the gel is above 90% when flushed with water at a flow rate of 10 m / min for 30 min at 50-180°C. After injection into the water-bearing formation, it can strongly reside around the wellbore and solidify under formation conditions to generate a plugging material with an overlap shear strength of 0.1-0.14 MPa and a compressive strength of not less than 16 MPa, ultimately plugging the lost formation.

[0015] (2) The crosslinkable polymer in the plugging composition of the present invention first undergoes a crosslinking reaction with the crosslinking agent to generate a gel, which encapsulates other components in the crosslinked network structure, so that the system will not be dispersed by water. The mass retention rate is more than 90% after being flushed by a water flow of 10 m / min for 30 min, and the pressure resistance can reach 7 MPa.

[0016] (3) Compared with existing sealing compositions, the sealing material formed by the sealing composition of the present invention has significant improvements in terms of water erosion resistance and high temperature resistance, and can be applied to sealing of water-bearing formations, especially sealing of formations containing flowing water at 50-180°C. Detailed Implementation

[0017] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0018] The first aspect of the present invention provides a plugging composition, which can crosslink to form a gel before or during injection into the formation, the gel can solidify at the site of the lost formation to form a plugging material, wherein the mass retention rate of the gel is above 90% after being flushed with water at a flow rate of 10 m / min for 30 min at 50-180°C; and the overlap shear strength of the plugging material is 0.1-0.14 MPa.

[0019] In this invention, the consistency of the system is tested using an OWC-9380B pressure thickener under the following conditions: temperature 100-180℃ and pressure 20-100MPa. The consistency of the sealing composition is <20BC, the consistency is 30-40BC (gel state), and the consistency is >70BC (fully cured sealing material).

[0020] In this invention, when the test temperature is below 100℃, the gelation stage and the complete curing stage can also be determined by the viscosity value. The instrument used for viscosity measurement is a Buchner DV-2 viscometer with a rotor of size 61-65 and a rotation speed of 1000 s. -1 After mixing the plugging composition, place it in a set temperature environment (e.g., the temperature corresponding to the formation). Measure the viscosity with a viscometer at regular intervals. Record the time when the viscosity value increases as the time of gel formation. Continue measuring until the viscosity value stabilizes and no longer increases, indicating complete curing. Record this as the time of complete curing.

[0021] In this invention, the mass retention rate of the gel after being flushed with a water flow rate of 10 m / min for 30 minutes is above 90%, for example, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, or any value within any range of any two of the above values, preferably 93-97%. The overlap shear strength of the sealing material is 0.1-0.14 MPa, for example, 0.1 MPa, 0.11 MPa, 0.12 MPa, 0.13 MPa, 0.14 MPa, or any value within any range of any two of the above values.

[0022] In this invention, the lap shear strength of the sealing material refers to the lap shear strength at the interface between the sealing material and the rock. A higher lap shear strength indicates a greater lap shear strength at the interface between the sealing material and the rock, and a less likely detachment of the sealing material from the rock interface.

[0023] In this invention, the mass retention rate reflects the resistance to water erosion and thinning. A higher mass retention rate indicates better resistance to water erosion and thinning, and vice versa.

[0024] In this invention, the mass retention rate is tested using a simulation device for plugging water-bearing lost circulation zones disclosed in CN113123756A. The formed gel is left to stand for 30 minutes. 500 mL of this gel is then taken and injected into the testing device under a water flow (see CN113123756A for details, Simulation Device for Plugging Water-Bearing Lost Circulation Zones). The water flow rate is set to 10 m / min, and the gel injection rate is 20 m / min. After gel injection, water flow continues for another 30 minutes. The sample is then removed, and the mass retention rate is calculated. Mass retention rate = (Mass of sample after flushing / Mass of injected gel) * 100%.

[0025] In some embodiments of the present invention, the pressure-bearing strength of the sealing material is not less than 7 MPa. For example, 7 MPa, 8 MPa, 9 MPa, 10 MPa, 11 MPa, 12 MPa, and any value within the range of any two of the above values, preferably 8-10 MPa.

[0026] In this invention, the pressure bearing strength is tested using the simulation device for plugging water-bearing leakage layers disclosed in CN113123756A. The maximum pressure value of the pressure gauge 17 is the pressure bearing strength of the plugging material.

[0027] In some embodiments of the present invention, the compressive strength of the sealing material is not less than 16 MPa, preferably 18-25 MPa.

[0028] In some embodiments of the present invention, the lost formation is an aquifer, preferably a formation containing flowing water.

[0029] In this invention, the lost formation location refers to the lost formation wellbore.

[0030] In some embodiments of the present invention, the temperature of the lost formation is 50-180°C.

[0031] In some embodiments of the present invention, the plugging composition comprises the following components: a crosslinkable polymer, a crosslinking agent and a reinforcing agent and a solvent; wherein the crosslinking agent contains a metal crosslinking agent and / or an allyl crosslinking agent, and the reinforcing agent is reinforcing agent I and / or reinforcing agent II;

[0032] The reinforcing agent I comprises the monomer shown in formula (I), dopamine, and an initiator;

[0033]

[0034] Among them, R1, R2, R 21 R 22 R 31 and R 32 Each is independently hydrogen or C1-C 10 Straight-chain or branched alkyl groups;

[0035] The reinforcing agent II includes a consolidating material and a retarder. The consolidating material is a material that can hydrate and solidify upon contact with water. The compressive strength of the consolidating material is >10MPa, and the expansion rate is 0.5-1.5%.

[0036] In this invention, the initiator in Reinforcing Agent I enables the polymerizable monomers to undergo secondary cross-linking and curing under controllable formation conditions, forming a plugging material at the site of leakage. The retarder in Reinforcing Agent II enables the solidified material to undergo controllable curing under formation conditions, forming a plugging material at the site of leakage.

[0037] In this invention, formation conditions refer to the conditions of the formation oil and gas well. In this invention, the formation conditions mainly consider temperature, because temperature has the greatest impact on initiators and retarders. The plugging composition of this invention has a good plugging effect at temperatures of 50-180℃.

[0038] In this invention, the crosslinkable polymer undergoes crosslinking upon contact with the crosslinking agent. This crosslinking can occur before or during injection, forming a gel. The gel retains over 90% of its mass after being flushed by a 10 m / min water flow for 30 minutes, making the system resistant to water runoff. Over time, the degree of crosslinking increases, enabling strong retention around the wellbore and ultimately forming a plugging material at the lost circulation zone. The overlap shear strength of this plugging material is 0.1-0.14 MPa. The plugging material formed by the plugging composition of this invention exhibits significant improvements in resistance to water runoff and high temperatures, making it suitable for water-bearing formations below 180°C, particularly formations containing flowing water.

[0039] In this invention, the C1-C 10 Examples of straight-chain or branched alkyl groups include, for example, any one of methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, tert-pentyl, neopentyl, n-hexyl, isohexyl, n-heptyl, isoheptyl, 2-methylhexyl, 2-ethylhexyl, 1-methylheptyl, 2-methylheptyl, n-octyl, isooctyl, n-nonyl, isononyl, and 3,5,5-trimethylhexyl.

[0040] In some preferred embodiments of the present invention, the monomer shown in formula (I) is acrylamide or a derivative thereof.

[0041] In this invention, the consolidating material in reinforcing agent II solidifies and exhibits good adhesion to the water-containing leak layer, forming a solidified plugging material that will not be washed away by water after entering the leak layer. The crosslinkable polymer first crosslinks with the crosslinking agent to form a gel, and then solidifies with the consolidating material to form the plugging material.

[0042] In this invention, when using the plugging composition, the amount and type of initiator, retarder or retarder can be controlled to cause it to solidify at the leakage stratum.

[0043] In some embodiments of the present invention, R1, R2, R 21 R 22 R 31 and R 32 Each of the components is independently hydrogen or a straight-chain or branched alkyl group of C1-C6, preferably hydrogen or a straight-chain or branched alkyl group of C1-C4, more preferably hydrogen, methyl or ethyl.

[0044] In some embodiments of the present invention, the metal crosslinking agent is selected from at least one of zirconium crosslinking agents, chromium crosslinking agents, and aluminum crosslinking agents.

[0045] In some embodiments of the present invention, the allyl crosslinking agent is selected from at least one of N,N'-methylenebisacrylamide, glycerol triacrylate, ethoxylated trimethylolpropane triacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, and ethoxylated pentaerythritol tetraacrylate.

[0046] In this invention, the crosslinking agent does not contain water-soluble carbon nanotube crosslinking agents. This invention achieves excellent crosslinking effects without the need for the addition of water-soluble carbon nanotube crosslinking agents.

[0047] In this invention, when preparing the sealing composition, the crosslinkable polymer can be added in the form of solid particles or water-in-oil emulsion. When the crosslinkable polymer is added in the form of solid particles, the sealing composition of this invention needs to contain a solvent (preferably water) to dissolve the solid substances in the composition. When the crosslinkable polymer is added in the form of water-in-oil emulsion, the solvent (preferably water) in the sealing composition of this invention is used to prepare the water-in-oil emulsion.

[0048] The plugging composition of this invention has low viscosity during formulation. After injection into the wellbore, during its flow in the wellbore, the crosslinkable polymer first crosslinks with the crosslinking agent to form a gel, which encapsulates other components within the crosslinked network structure, forming a unified whole that is not diluted or dispersed by water. Because the gel contains a large number of hydrogen bonds and has a certain density, it can adhere to the leaking layer and remain around the wellbore. Under the temperature and pressure conditions of the formation, the initiator in reinforcing agent I initiates the polymerization and crosslinking of the monomers and dopamine shown in formula (I) in the system, further generating a multi-crosslinked plugging material with high compressive strength, thereby plugging the water-bearing leaking layer. The dopamine in the plugging composition enhances the adhesion of the gel to the rock, resulting in better adhesion to the leaking layer after gel curing, thus improving the water erosion resistance of the final plugging material.

[0049] In this invention, the sealing composition can undergo a first cross-linking at a certain temperature to form a gel, and then undergo a second cross-linking to generate a solid, non-flowing body to achieve complete curing.

[0050] In some embodiments of the present invention, the crosslinkable polymer is polyacrylamide and / or a polyacrylamide derivative, and the solvent is water; the plugging composition comprises the following components in parts by weight: 0.01-8 parts of crosslinkable polymer, 0.01-8 parts of metal crosslinking agent, 0.01-0.9 parts of allyl crosslinking agent, 3-30 parts of monomer shown in formula (I), 0.01-3 parts of dopamine, 0.01-8 parts of initiator, and 100 parts of water.

[0051] In this invention, the polyacrylamide and / or polyacrylamide derivatives are in the form of solid granules, which need to be dissolved in water first before being mixed with the remaining components.

[0052] When the present invention selects each component according to the above-mentioned specific weight parts to formulate the leak-sealing composition, a higher mass retention rate can be obtained during implementation, the resulting leak-sealing material has stronger compressive strength and better adaptability to high-temperature environments.

[0053] In this invention, the crosslinkable polymer is preferably polyacrylamide, and its weight parts can be 0.01 parts, 0.5 parts, 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, and any value within the range of any two of the above values.

[0054] In this invention, the weight parts of dopamine can be 0.01 parts, 0.5 parts, 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, or any value within the range of any two of the above values.

[0055] In this invention, the weight parts of the metal crosslinking agent can be 0.01 parts, 0.5 parts, 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, or any value within the range of any two of the above values.

[0056] In this invention, the weight parts of the monomer shown in formula (I) can be 3 parts, 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, or any value within the range of any two of the above values.

[0057] In this invention, the initiator may be 0.01, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8 parts by weight, or any value within the range of any two of the above values.

[0058] In this invention, the allyl crosslinking agent is 0.01, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, or 0.9 parts, or any value within the range of any two of the above values.

[0059] In some preferred embodiments, the components in the sealing composition are in the following weight proportions: 0.01-5 parts polyacrylamide, 0.01-1 parts dopamine, 0.01-5 parts metal crosslinking agent, 5-25 parts monomer of formula (I), 0.01-5 parts initiator, 0.01-0.5 parts allyl crosslinking agent, and 100 parts water.

[0060] In some embodiments of the present invention, polyacrylamide and dopamine are dissolved in water, and metal crosslinking agents, monomers, allyl crosslinking agents and initiators are added respectively. The mixture is then mixed evenly to obtain the corresponding sealing slurry of the above-mentioned sealing composition.

[0061] In some embodiments of the present invention, the weight-average molecular weight of the crosslinkable polymer is 2.5 million to 18 million g / mol, for example, 2.5 million g / mol, 4 million g / mol, 6 million g / mol, 8 million g / mol, 10 million g / mol, 12 million g / mol, 14 million g / mol, 16 million g / mol, 18 million g / mol, and any value within any range of two of the above values, preferably 3 million to 16 million g / mol. The preferred weight-average molecular weight of the polyacrylamide enables the obtained gel to have higher mass retention and retention capacity under flowing water conditions.

[0062] In this invention, the weight-average molecular weight of the polymer is determined by gel permeation chromatography.

[0063] In some embodiments, the metal crosslinking agent is selected from at least one of zirconium crosslinking agents, chromium crosslinking agents, and aluminum crosslinking agents. During the implementation of the leak-sealing composition of the present invention, polyacrylamide first crosslinks with the metal crosslinking agent to form a gel.

[0064] In some preferred embodiments, the zirconium crosslinking agent is zirconium trichloride and / or zirconium oxychloride.

[0065] In some preferred embodiments, the chromium crosslinking agent is chromium lactate and / or chromium chloride.

[0066] In some preferred embodiments, the aluminum crosslinking agent is aluminum citrate.

[0067] In some preferred embodiments, the allyl crosslinking agent is selected from at least one of N,N'-methylenebisacrylamide, glycerol triacrylate, ethoxylated trimethylolpropane triacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, and ethoxylated pentaerythritol tetraacrylate.

[0068] In some preferred embodiments, the crosslinking agent further includes a silicone crosslinking agent. When the plugging composition of the present invention includes a silicone crosslinking agent, the strength of the system can be improved, and the adhesion between the gel and the formation can be increased.

[0069] In some preferred embodiments, the silicon crosslinking agent is selected from at least one of water glass, ethyl silicate, and γ-methacryloyloxypropyltrimethoxysilane (KH570).

[0070] In some preferred embodiments, the silicon crosslinking agent is 0.05-12 parts by weight, for example 0.05 parts, 0.5 parts, 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, and any value within the range of any two of the above values, preferably 0.1-10 parts.

[0071] In some preferred embodiments, the initiator is selected from at least one of potassium persulfate, ammonium persulfate, sodium persulfate, benzoyl peroxide, azobisisobutyramidine hydrochloride, di-tert-butyl peroxide, dodecyl peroxide, azobisisobutyronitrile, and cumene hydroperoxide. These initiators are adaptable to different temperatures and can efficiently initiate cross-linking reactions at various temperatures, allowing the gel to further develop into a multi-crosslinked non-gel with high compressive strength.

[0072] In some embodiments of the present invention, the reinforcing agent I further includes at least one of the monomers shown in formula (II), (III), (IV), (V), and (VI): preferably, it simultaneously includes the monomers shown in formula (II), (III), (IV), (V), and (VI).

[0073]

[0074] Among them, R3, R4, R6, R7, R 11 R 12 R 13 R 14 R 15 R 16 R 18 R 19 and R 20 Each is independently hydrogen or C1-C 10 Straight-chain or branched alkyl groups; R5 and R 17 Each independently is C1-C 20 Straight-chain or branched alkylene groups; R8, R9 and R 10 One of them is C1-C 20 The chain consists of a straight-chain or branched alkyl group, with the other two being hydrogen or C1-C2 respectively. 10 Straight-chain or branched alkyl groups; R' is C1-C 10 The linear or branched alkylene groups; M1 and M2 are each independently H, Na, Li or K; M1 is preferably H or Na; M2 is preferably Na; X1 and X2 are each independently selected from Cl, Br or I, X1 is preferably Cl, X2 is preferably Cl; m is any integer from 4 to 20, and n is any integer from 3 to 10.

[0075] In some preferred embodiments, R3, R4, R6, R7, R 11 R 12 R 13 R 14 R 15 R 16 R 18 R 19 and R 20 Each of the components is independently hydrogen or a straight-chain or branched alkyl group of C1-C6, preferably hydrogen or a straight-chain or branched alkyl group of C1-C4, more preferably hydrogen, methyl or ethyl.

[0076] In some preferred embodiments, R5 and R 17 Each independently is C1-C 20 The linear or branched alkylene groups, including but not limited to: methylene, ethylene, propylene, isopropylene, butylene, isobutylene, tert-butylene, pentylene, and hexylene; R5 is preferably isobutylene; R 17 Ethylene is preferred.

[0077] In some preferred embodiments, R' is C1-C 10 The straight-chain or branched alkylene groups include, but are not limited to: methylene, ethylene, propylene, isopropylene, butylene, isobutylene, tert-butylene, pentylene, and hexylene; R' is preferably methylene.

[0078] In some preferred embodiments, R8, R9 and R 10 One of them is C8-C 20 Straight-chain or branched alkyl groups, preferably C 18 One is a straight-chain or branched alkyl group, and the other two are methyl groups.

[0079] In some embodiments, the monomer shown in formula (II) is 2-acrylamido-2-methylpropanesulfonic acid and / or sodium 2-acrylamido-2-methylpropanesulfonate, the monomer shown in formula (III) is octadecyl dimethyl allyl ammonium chloride, the monomer shown in formula (IV) is allyl nonylphenol polyoxyethylene ether, the monomer shown in formula (V) is sodium acrylate, and the monomer shown in formula (VI) is acryloyloxyethyl trimethyl ammonium chloride.

[0080] In some preferred embodiments, based on 100 parts by weight of water, the monomer shown in formula (II) is 0.2-25 parts by weight, preferably 2-20 parts by weight.

[0081] In some preferred embodiments, based on 100 parts by weight of water, the monomer shown in formula (III) is 0.5-20 parts by weight, preferably 1-15 parts by weight.

[0082] In some preferred embodiments, based on 100 parts by weight of water, the monomer shown in formula (IV) is 0.2-5 parts by weight, preferably 0.5-4 parts by weight.

[0083] In some preferred embodiments, based on 100 parts by weight of water, the monomer shown in formula (V) is 0.5-20 parts by weight, preferably 1-15 parts by weight.

[0084] In some preferred embodiments, based on 100 parts by weight of water, the monomer shown in formula (VI) is 0.5-10 parts by weight, preferably 1-8 parts by weight.

[0085] In some preferred embodiments, the sealing composition further includes a weighting agent; preferably, the weighting agent is selected from at least one of calcium carbonate, barite, and iron ore powder, and more preferably barite.

[0086] In some preferred embodiments, the weighting agent is 5-200 parts by weight, preferably 10-150 parts by weight, based on 100 parts by weight of water.

[0087] In some embodiments, the plugging composition further includes a retarder.

[0088] In some preferred embodiments, the retarder is p-benzoquinone.

[0089] In some preferred embodiments, the retarder is no more than 1 part by weight of 100 parts by weight of water, preferably 0.1-0.6 parts by weight.

[0090] The plugging composition has a density of 1-2 g / cm³ at 25°C. 3 The preferred value is 1.2-1.65 g / cm³. 3 .

[0091] In other embodiments of the present invention, the crosslinkable polymer is polyacrylamide and / or a polyacrylamide derivative, and the crosslinkable polymer exists in the form of a water-in-oil emulsion, the water-in-oil emulsion comprising the crosslinkable polymer, oil, water and an emulsifier; the weight parts of each component in the plugging composition are as follows: 100 parts of water-in-oil emulsion, 0.01-8 parts of crosslinking agent, 3-30 parts of monomer shown in formula (I), 0.01-2 parts of dopamine and 0.01-8 parts of initiator.

[0092] In some preferred embodiments of the present invention, the mass ratio of the crosslinkable polymer, oil, water, and emulsifier is 0.5-15:100:50-100:0.05-10, for example, 0.5:100:50:0.05, 3:100:60:3, 10:100:80:7, 13:100:90:2, 8:100:92:5, 15:100:10:10, and any value within the range of any two of the above values, more preferably 1-10:100:60-90:0.1-5. The above mass ratios enable the obtained strong gel to have a higher mass retention rate.

[0093] In this invention, the water-in-oil emulsion is prepared by a method including the following steps:

[0094] First, add polyacrylamide and / or polyacrylamide derivatives to water and stir. Then, introduce the emulsifier into the oil phase and stir to dissolve. Next, slowly add the polyacrylamide solution and / or polyacrylamide derivative solution to the oil phase and stir to emulsify at a stirring speed of 8000-12000 r / min to obtain a water-in-oil emulsion.

[0095] When polyacrylamide and polyacrylamide derivatives are in the form of a water-in-oil emulsion, after the plugging composition enters the leaking layer and encounters formation water, the water-in-oil emulsion breaks down, and polyacrylamide and polyacrylamide derivatives are immediately released to crosslink with the crosslinking agent in the system to form a gel. The monomers and initiators are encapsulated in the crosslinked network structure, so that the system will not be washed away by water.

[0096] In some preferred embodiments, the oil is selected from at least one of waste white oil, waste diesel oil, waste engine oil, and waste edible oil. The oil in the water-in-oil emulsion of the present invention can utilize the waste oil phase, turning waste into a valuable resource.

[0097] In some preferred embodiments, the polyacrylamide is anionic polyacrylamide, and the weight-average molecular weight of the anionic polyacrylamide is 2.5 million to 10 million g / mol, such as 2.5 million g / mol, 4 million g / mol, 6 million g / mol, 8 million g / mol, 10 million g / mol, and any value within the range of any two of the above values, preferably 3 million to 8 million g / mol.

[0098] In this invention, the weight-average molecular weight of the polymer is determined by gel permeation chromatography.

[0099] In some preferred embodiments, the emulsifier is selected from at least one of octylphenol polyoxyethylene ether-10 (OP-10), octylphenol polyoxyethylene ether-15 (OP-15), nonylphenol polyoxyethylene ether-10 (NP-10), nonylphenol polyoxyethylene ether-15 (NP-15), Tween-20 (T-20), Tween-60 (T-60), Span-80 (S-80), Span-85 (S-85), and sodium dodecylbenzenesulfonate.

[0100] In some embodiments of the present invention, the reinforcing agent I further includes at least one of the monomers shown in formula (II), (III), (IV), (V), and (VI): preferably, it simultaneously includes the monomers shown in formula (II), (III), (IV), (V), and (VI).

[0101]

[0102] Among them, R3, R4, R6, R7, R 11 R 12 R 13 R 14 R 15 R 16 R 18 R 19 and R 20 Each is independently hydrogen or C1-C 10 Straight-chain or branched alkyl groups; R5 and R 17 Each independently is C1-C 20 Straight-chain or branched alkylene groups; R8, R9 and R 10 One of them is C1-C 20 The chain consists of a straight-chain or branched alkyl group, with the other two being hydrogen or C1-C2 respectively. 10 Straight-chain or branched alkyl groups; R' is C1-C 10 The linear or branched alkylene groups; M1 and M2 are each independently H, Na, Li or K; M1 is preferably H or Na; M2 is preferably Na; X1 and X2 are each independently selected from Cl, Br or I, X1 is preferably Cl, X2 is preferably Cl; m is any integer from 4 to 20, and n is any integer from 3 to 10.

[0103] For the specific preferred embodiments of each substituent, please refer to the preceding description, which will not be repeated here.

[0104] In some embodiments, the monomer shown in formula (II) is 2-acrylamido-2-methylpropanesulfonic acid and / or sodium 2-acrylamido-2-methylpropanesulfonate, the monomer shown in formula (III) is octadecyl dimethyl allyl ammonium chloride, the monomer shown in formula (IV) is allyl nonylphenol polyoxyethylene ether, the monomer shown in formula (V) is sodium acrylate, and the monomer shown in formula (VI) is acryloyloxyethyl trimethyl ammonium chloride.

[0105] In some preferred embodiments, based on 100 parts by weight of water-in-oil emulsion, the monomer shown in formula (II) is 0.2-20 parts by weight, preferably 2-15 parts by weight.

[0106] In some preferred embodiments, based on 100 parts by weight of water-in-oil emulsion, the monomer shown in formula (III) is 0.5-20 parts by weight, preferably 1-15 parts by weight.

[0107] In some preferred embodiments, based on 100 parts by weight of water-in-oil emulsion, the monomer shown in formula (IV) is 0.2-5 parts by weight, preferably 0.5-4 parts by weight.

[0108] In some preferred embodiments, based on 100 parts by weight of water-in-oil emulsion, the monomer shown in formula (V) is 0.5-20 parts by weight, preferably 1-15 parts.

[0109] In some preferred embodiments, based on 100 parts by weight of water-in-oil emulsion, the monomer shown in formula (VI) is 0.5-10 parts by weight, preferably 1-8 parts by weight.

[0110] In this invention, an oil-in-water emulsion, monomer, initiator, and crosslinking agent are mixed and stirred evenly to obtain the corresponding sealing slurry of the above-mentioned sealing composition.

[0111] When the present invention selects each component according to the above-mentioned specific weight parts to formulate the leak-sealing composition, a higher mass retention rate can be obtained during implementation, the resulting leak-sealing material has stronger compressive strength and better adaptability to high-temperature environments.

[0112] The weight parts of the monomer shown in formula (I) can be 3 parts, 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, or any value within the range of any two of the above values.

[0113] The initiator may be in the following weight proportions: 0.01 parts, 0.5 parts, 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, or any value within the range of any two of the above values.

[0114] The weight parts of the crosslinking agent can be 0.01 parts, 0.5 parts, 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, or any value within the range of any two of the above values.

[0115] In some preferred embodiments, the components in the sealing composition are in the following weight proportions: 100 parts of water-in-oil emulsion, 5-25 parts of the monomer shown in formula (I), 0.01-1 part of dopamine, 0.01-5 parts of initiator and 0.01-5 parts of crosslinking agent.

[0116] In some preferred embodiments of the present invention, the initiator is selected from at least one of potassium persulfate, ammonium persulfate, sodium persulfate, benzoyl peroxide, azobisisobutyramidine hydrochloride, di-tert-butyl peroxide, dodecyl peroxide, azobisisobutyronitrile, and cumene hydroperoxide. The above-mentioned preferred initiators are adaptable to different temperatures and can efficiently initiate cross-linking reactions at different temperatures, allowing the gel to further form a multi-crosslinked gel with high compressive strength.

[0117] In some preferred embodiments, the crosslinking agent comprises an allyl crosslinking agent and / or an organometallic crosslinking agent.

[0118] In some preferred embodiments, the crosslinking agent comprises a mixture of allyl crosslinking agents and organometallic crosslinking agents, wherein the mass ratio of allyl crosslinking agent to organometallic crosslinking agent is 1:0.3-8, preferably 1:0.5-5.

[0119] In some preferred embodiments, the allyl crosslinking agent is selected from at least one of N,N'-methylenebisacrylamide, glycerol triacrylate, ethoxylated trimethylolpropane triacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, and ethoxylated pentaerythritol tetraacrylate.

[0120] In some preferred embodiments, the organometallic crosslinking agent is selected from at least one of organozzirconium crosslinking agents, organochromium crosslinking agents, and organoaluminum crosslinking agents.

[0121] In some preferred embodiments, the organozirconium crosslinking agent is zirconium citrate.

[0122] In some preferred embodiments, the organic chromium crosslinking agent is chromium lactate.

[0123] In some preferred embodiments, the organoaluminum crosslinking agent is aluminum citrate.

[0124] In some preferred embodiments, the crosslinking agent further includes a silicone crosslinking agent.

[0125] When the crosslinking agent of the present invention includes a silicon crosslinking agent, the strength of the system can be improved, and the adhesion between the gel and the formation can be increased.

[0126] In some preferred embodiments, the silicon crosslinking agent is selected from at least one of water glass, ethyl silicate, and γ-methacryloyloxypropyltrimethoxysilane (KH570).

[0127] In some preferred embodiments, the crosslinking agent is a mixture of allyl crosslinking agents, organometallic crosslinking agents and silicone crosslinking agents, wherein the mass ratio of allyl crosslinking agent, organometallic crosslinking agent and silicone crosslinking agent is 1:0.3-8:0.1-12, preferably 1:0.5-5:0.2-10.

[0128] In some preferred embodiments, the sealing composition further includes a weighting agent.

[0129] In some preferred embodiments, the weighting agent is selected from at least one of calcium carbonate, barite, and iron ore powder, preferably barite.

[0130] In some preferred embodiments, based on 100 parts by weight of water-in-oil emulsion, the weighting agent is 5-120 parts by weight, preferably 10-100 parts by weight.

[0131] In some embodiments, the plugging composition further includes a retarder.

[0132] In some preferred embodiments, the retarder is p-benzoquinone.

[0133] In some preferred embodiments, based on 100 parts by weight of water-in-oil emulsion, the retarder is no more than 1 part by weight, preferably 0.1-0.6 parts.

[0134] In some preferred embodiments, the sealing composition has a density of 1.2-1.78 g / cm³ at 25°C. 3 .

[0135] In some embodiments of the present invention, the sealing composition further includes a salt-resistant polymer, wherein the salt-resistant polymer and the crosslinkable polymer constitute a water-indispersible material; the weight parts of each component in the sealing composition are as follows: 10-15 parts of water-indispersible material, 0.1-4 parts of crosslinking agent, 50-200 parts of consolidating material and 100 parts of water.

[0136] In this invention, preferably, the plugging composition comprises, by weight: 12-15 parts of water-insoluble material, 1-3 parts of crosslinking agent, 150-200 parts of consolidating material, 0.5-5 parts of retarder, and 100 parts by weight of water. Using these preferred conditions is beneficial for improving the performance of the consolidated plugging grout, namely, giving it high-quality retention rate, high adhesion, and high compressive strength.

[0137] When the present invention selects each component according to the above-mentioned specific weight parts to formulate the leak-sealing composition, a higher mass retention rate can be obtained during implementation, the resulting leak-sealing material has stronger compressive strength and better adaptability to high-temperature environments.

[0138] In some preferred embodiments, the crosslinkable polymer is a nonionic polymer, preferably selected from polyacrylamide and / or polyacrylamide derivatives.

[0139] In some preferred embodiments, the weight-average molecular weight of the crosslinkable polymer is 2 million to 14 million g / mol, for example, 2 million g / mol, 2.5 million g / mol, 3 million g / mol, 4 million g / mol, 5 million g / mol, 6 million g / mol, 7 million g / mol, 8 million g / mol, 9 million g / mol, 10 million g / mol, 12 million g / mol, 14 million g / mol, and any value within any range of two of the above values, preferably 5 million to 14 million g / mol. The preferred weight-average molecular weight of the polyacrylamide and polyacrylamide derivatives enables the obtained gel to have higher mass retention and retention capacity under flowing water conditions.

[0140] In this invention, the weight-average molecular weight of the polymer is determined by gel permeation chromatography.

[0141] In some preferred embodiments, the salt-resistant polymer is selected from at least one of SMPFL-C, SMHV-C, and SMVIS-1.

[0142] In this invention, SMPFL-C, SMHV-C, and SMVIS-1 were purchased from China Petroleum Engineering Technology Research Institute Co., Ltd.

[0143] In this invention, the water-insoluble material comprises a salt-resistant polymer and a nonionic polymer; the mass ratio of the salt-resistant polymer to the nonionic polymer is 10:(0.5-3), preferably 10:(1-2). The combination of the salt-resistant polymer and the nonionic polymer helps to improve the mass retention rate of the solidified plugging grout, allowing it to remain in the leak layer under flowing water conditions without being washed away by the water.

[0144] In this invention, the preparation method of the water-indispersible material has a wide range of options, as long as the weight ratio of each component in the water-indispersible material meets the above-mentioned limitations.

[0145] In some preferred embodiments, the consolidating material includes cement or lime, slag, bentonite, gypsum, and an acidic substance; the acidic substance is hydrochloric acid and / or hydroxyethylidene diphosphonic acid.

[0146] In some preferred embodiments, the mass ratio of the cement or lime, slag, bentonite, gypsum and acidic substance is 4-10:8-20:1-2:1-3:0.2-1.

[0147] In this invention, under the action of the crosslinking agent, the bonding performance between the solidified material and the water-containing leakage layer is good after the solidification material is cured.

[0148] In some preferred embodiments, the retarder is selected from 2-acrylamide-2-methylpropanesulfonic acid polymers and / or hydroxycarboxylic acid polymers.

[0149] Furthermore, the weight-average molecular weight of the 2-acrylamide-2-methylpropanesulfonic acid polymer is 1,000,000 to 5,000,000 g / mol.

[0150] Furthermore, the hydroxycarboxylic acid polymer may be SCR-3, wherein SCR-3 is a hydroxycarboxylic acid polymer produced by Sinopec Petroleum Engineering Technology Research Institute Co., Ltd.

[0151] In this invention, based on 100 parts by weight of water, the weight of the retarder is no more than 5 parts, preferably 0.1-2 parts.

[0152] In some preferred embodiments, the plugging composition further includes 0-40 parts by weight of a density modifier, based on 100 parts by weight of water.

[0153] In some preferred embodiments, the density regulator may be a weighting agent or a weight-reducing agent; the weighting agent is at least one of calcium carbonate, barite, or iron ore powder; the weight-reducing agent is at least one of cenospheres, hollow glass microspheres, and polymer hollow microspheres. All of the above components are commercially available. The density of the sealing composition can be adjusted by changing the amount of density regulator added.

[0154] In some embodiments of the present invention, the density of the sealing composition after mixing is 1-2 g / cm³ at 25°C. 3 The preferred value is 1.2-1.65 g / cm³. 3 .

[0155] In this invention, unless otherwise specified, the density is measured using the method of GB / T16783.1-2014.

[0156] A second aspect of the present invention provides a sealing material, which is obtained by curing the aforementioned sealing composition.

[0157] In some embodiments of the present invention, the curing temperature is 50-180°C.

[0158] In some embodiments of the present invention, the compressive strength of the sealing material is 15-25 MPa.

[0159] A third aspect of the present invention provides the application of the aforementioned plugging composition or the aforementioned plugging material in oil well formation plugging; preferably, the oil well formation is a water-bearing oil well formation at 50-180°C.

[0160] The sealing composition of the present invention forms a sealing material that is resistant to water runoff and high temperature. After entering aquifers, especially aquifers with flowing water, it can remain in the leaking layer and eventually solidify under the conditions of the formation to form a plug with a compressive strength of 15-25 MPa, thereby solving the leakage problem in aquifers with flowing water.

[0161] After the plugging composition of the present invention is injected into the water-bearing formation, polyacrylamide and / or polyacrylamide derivatives first undergo a cross-linking reaction with a cross-linking agent to generate a gel, which encapsulates other components in the cross-linked network structure, so that the system will not be washed away by water. After residence, under the temperature and pressure environment of the formation, polymerization is initiated by an initiator and cross-linking or solidification of the material occurs, further generating a multi-cross-linked plugging material with high compressive strength, thereby plugging the water-bearing leaking layer.

[0162] The sealing composition of the present invention is applicable to any water-bearing formation and has a significantly better effect than existing sealing compositions for formations with flowing water over a wide temperature range.

[0163] When the plugging composition or plugging material of this invention is used to plug formation fractures, especially those in formations containing flowing water, it can exhibit high compressive strength in formation environments at different temperatures, thereby solving the leakage problem in water-bearing formations.

[0164] A fourth aspect of the present invention provides a method for plugging leaks in oil wells. The method includes directly injecting the aforementioned plugging composition into formation fractures in the oil well, causing the plugging composition to form a gel during the injection process, or injecting the aforementioned plugging composition into formation fractures after it has formed a gel, wherein, under formation conditions, the gel solidifies at the site of the leak to form a plugging material; wherein the gel retains more than 90% of its mass after being flushed with water at a flow rate of 10 m / min for 30 minutes at 50-180°C; and the overlap shear strength of the plugging material is 0.1-0.14 MPa.

[0165] In the injection process of the plugging composition of the present invention, polyacrylamide and / or polyacrylamide derivatives first undergo a cross-linking reaction with a cross-linking agent to generate a gel, which encapsulates other components in the cross-linked network structure, preventing the system from being washed away by water and achieving a water erosion resistance mass retention rate of up to 96%. The gel formed in the present invention can strongly adhere around the wellbore and solidify under the temperature and pressure environment of the formation, generating a plugging material with a strength of up to 25 MPa, ultimately sealing the lost circulation layer.

[0166] Compared to existing sealing compositions, the sealing material formed by the sealing composition of the present invention exhibits significant improvements in resistance to water runoff and high temperatures. The sealing material of the present invention is suitable for water-bearing formations with temperatures ranging from 50 to 180°C, particularly formations containing flowing water.

[0167] In this invention, a suitable plugging composition is selected based on the geological conditions at the site. Considering that temperature has the greatest impact on the reaction, the simulated geological conditions mainly consider the geological temperature. Given that the underground is a confined space, the formation of gel and solidification can be simulated under confined conditions at a certain temperature or by injecting it into water at a certain temperature. If the plugging mixture can form a gel and solidify under confined conditions at a certain temperature, it is assumed that it will also form a gel and solidify under similar geological conditions. Simultaneously, water flushing is used to simulate a formation containing flowing water.

[0168] Unless otherwise specified in the following examples and comparative examples, all conditions were performed under standard conditions or conditions recommended by the manufacturer. Reagents or instruments used, unless otherwise specified, are all commercially available products.

[0169] SMHD-1, a chemically consolidated material, is a commercially available product of China Petroleum Engineering Technology Research Institute Co., Ltd.

[0170] SMHD-2, a chemically consolidated material, is a commercially available product of China Petroleum Engineering Technology Research Institute Co., Ltd.

[0171] SMPFL-C is a commercially available product of China Petroleum Engineering Technology Research Institute Co., Ltd.

[0172] SMHV-C is a commercially available product of China Petroleum Engineering Technology Research Institute Co., Ltd.

[0173] SMVIS-1 is a commercially available product of China Petroleum Engineering Technology Research Institute Co., Ltd.

[0174] Test method:

[0175] Density: Tested using a densitometer according to the method in GB / T 16783.1-2014.

[0176] Compressive strength: Tested according to the method in GB / T 50266-99.

[0177] Overlap shear strength: The test was conducted using the GB 7124-1986 method for determining the tensile shear strength of adhesives. The difference was that the metal was replaced with core pieces of the same specifications. The gel was applied to the overlapping area of ​​the limestone core pieces, and two such core pieces were gently covered and pressed under a pressure of 0.5 MPa for 1 hour. The overlap shear strength of the cured samples was then measured.

[0178] Compressive strength: After the formed gel has been left to stand for 30 minutes, take 500 mL of the gel and inject it into the test device (see CN113123756A for details, a simulation device for plugging water-bearing leakage layers) under water flow. Set the water flow rate to 10 m / min and the gel injection rate to 20 m / min. After the gel injection is complete, continue to inject water and wait until the formed gel is completely solidified. Continue to inject water and read the maximum pressure value of pressure gauge 17 (as shown in Figure 1 of CN113123756A). This value is the compressive strength of the solidified sample.

[0179] Mass retention rate: After the formed gel is left to stand for 30 minutes, 500 mL of the gel is taken and injected into the test device (see CN113123756A for details, a simulation device for plugging water-bearing leakage layers) under water flow. The water flow rate is set to 10 m / min and the gel injection rate is set to 20 m / min. After the gel injection is completed, water flow is continued for 30 minutes. Then the sample after rinsing is taken out and the mass retention rate of the sample is calculated.

[0180] Mass retention rate = (mass of sample after rinsing / mass of injected gel) * 100%.

[0181] Example 1

[0182] The sealing slurry was prepared according to the formulation of the sealing composition in Example 1 of Table 1. The specific preparation method is as follows: Weigh 100 parts of water, add 0.01 parts of polyacrylamide, stir at 1000 r / min until completely dissolved, then add 0.01 parts of zirconium oxychloride and stir for 5 min, then add 1 part of dopamine and stir for 5 min. Then, add 0.005 parts of ethoxylated trimethylolpropane triacrylate, 0.005 parts of pentaerythritol tetraacrylate, 10 parts of acrylamide, 2 parts of 2-acrylamide-2-methylpropanesulfonic acid, 3 parts of octadecyl dimethyl allyl ammonium chloride, 0.5 parts of allyl nonylphenol polyoxyethylene ether, 0.1 parts of ethyl silicate, 0.01 parts of azobisisobutyronitrile, and 10 parts of iron ore powder to the above solution in sequence, and stir and mix evenly to obtain the sealing slurry.

[0183] The density of the sealing grout at 25°C was 1.3 g / cm³, as determined by the aforementioned method. 3 Under sealed conditions at 100℃, the sealing grout gelled in 15 minutes and fully cured in 30 minutes. Using a testing device, the formed gel was flushed with water, and its mass retention rate was calculated to be 95%. After the gel fully cured to form the sealing material, its compressive strength was tested to be 7 MPa, its lap shear strength to be 0.11 MPa, and its compressive strength to be 22.3 MPa.

[0184] Example 2

[0185] Following the method of Example 1, the sealing slurry was prepared according to the formulation of the sealing composition in Example 2 of Table 1.

[0186] The density of the sealing grout at 25°C was 1.5 g / cm³, as determined by the aforementioned method. 3 Under sealed conditions at 80℃, the sealing grout gelled in 22 minutes and fully cured in 60 minutes. Using a testing device, the formed gel was flushed with water, and its mass retention rate was calculated to be 93%. After the gel fully cured to form the sealing material, its compressive strength was tested to be 7 MPa, its lap shear strength to be 0.10 MPa, and its compressive strength to be 24.1 MPa.

[0187] Example 3

[0188] Following the method of Example 1, the sealing slurry was prepared according to the formulation of the sealing composition in Example 3 of Table 1.

[0189] The density of the sealing grout at 25°C was 1.2 g / cm³, as determined by the aforementioned method. 3 Under sealed conditions at 50℃, the sealing grout gelled in 15 minutes and fully cured in 80 minutes. Using a testing device, the formed gel was flushed with water, and its mass retention rate was calculated to be 96%. After the gel fully cured to form the sealing material, its compressive strength reached 7 MPa, its lap shear strength was 0.13 MPa, and its compressive strength was 25 MPa.

[0190] Example 4

[0191] The sealing slurry was prepared according to the method of Example 1 and the formulation of the sealing composition in Example 4 of Table 1.

[0192] The density of the sealing grout at 25°C was 1.38 g / cm³, as determined by the aforementioned method. 3Under sealed conditions at 120℃, the sealing grout gelled in 23 minutes and fully cured in 67 minutes. Using a testing device, the formed gel was flushed with water, and its mass retention rate was calculated to be 94.7%. After the gel fully cured to form the sealing material, its compressive strength was tested to be 7 MPa, its lap shear strength to be 0.12 MPa, and its compressive strength to be 21.9 MPa.

[0193] Example 5

[0194] Following the method of Example 1, the sealing slurry was prepared according to the formulation of the sealing composition in Example 5 of Table 1.

[0195] The density of the sealing grout at 25°C was 1.65 g / cm³, as determined by the aforementioned method. 3 Under sealed conditions at 150℃, the sealing grout gelled in 10 minutes and fully cured in 30 minutes. Using a testing device, the formed gel was flushed with water, and its mass retention rate was calculated to be 93.7%. After the gel fully cured to form the sealing material, its compressive strength was tested to be 7 MPa, its lap shear strength to be 0.14 MPa, and its compressive strength to be 22.8 MPa.

[0196] Example 6

[0197] Following the method of Example 1, the sealing slurry was prepared according to the formulation of the sealing composition in Example 3 of Table 1, except that no silicone crosslinking agent was added.

[0198] The density of the sealing grout at 25°C was 1.2 g / cm³, as determined by the aforementioned method. 3 Under sealed conditions at 50℃, the sealing grout gelled in 15 minutes and fully cured in 80 minutes. Using a testing device, the formed gel was flushed with water, and its mass retention rate was calculated to be 90%. After the gel fully cured to form the sealing material, its compressive strength was tested to be 7 MPa, its lap shear strength to be 0.11 MPa, and its compressive strength to be 18 MPa.

[0199] Comparative Example 1

[0200] Following the method of Example 1, the sealing slurry was prepared according to the formulation of the sealing composition in Example 3 of Table 1, except that dopamine was not added.

[0201] The density of the sealing grout at 25°C was 1.2 g / cm³, as determined by the aforementioned method. 3Under sealed conditions at 50℃, the gel formation time of the sealing slurry was 20 minutes, and the complete curing time was 90 minutes. Using a testing device, the formed gel was flushed with water, and the calculated mass retention rate was only 65%. After the gel completely cured to form the sealing material, its compressive strength was only 1.2 MPa, its lap shear strength was only 0.016 MPa, and its compressive strength was 12 MPa. It is evident that the final sealing material has poor retention properties in flowing water leaks.

[0202] Table 1

[0203]

[0204]

[0205] Example 7

[0206] Prepare the sealing slurry according to the formulation of the sealing composition in Example 7 of Table 2.

[0207] (1) Preparation of water-in-oil emulsion:

[0208] First, 5 parts of anionic polyacrylamide with a weight average molecular weight of 3 million g / mol were added to 90 parts of water and stirred to dissolve, thus obtaining a polyacrylamide solution. Then, 3 parts of emulsifier OP-10 were added to 100g of waste white oil and stirred to dissolve, thus obtaining an oil phase. The obtained polyacrylamide solution was then slowly added to the obtained oil phase and stirred and emulsified at a stirring speed of 8000 r / min to obtain a water-in-oil emulsion.

[0209] (2) Preparation of sealing grout:

[0210] The water-in-oil emulsion obtained in step (1) is mixed evenly with other components to obtain a plugging slurry.

[0211] The density of the sealing grout at 25°C was 1.05 g / cm³, as determined by the aforementioned method. 3 The obtained sealing grout was injected into 60°C water. The grout gelled in 45 seconds and fully cured in 40 minutes. Using a testing device, the formed gel was flushed with water, and its mass retention rate was calculated to be 97.5%. After the gel fully cured to form the sealing material, its compressive strength was tested to be 7 MPa, its lap shear strength to be 0.13 MPa, and its compressive strength to be 18.8 MPa.

[0212] Example 8

[0213] Prepare the sealing slurry according to the formulation of the sealing composition in Example 8 of Table 2.

[0214] (1) Preparation of water-in-oil emulsion:

[0215] First, 4 parts of anionic polyacrylamide with a weight average molecular weight of 4 million g / mol were added to 80 parts of water and stirred to dissolve, thus obtaining a polyacrylamide solution. Then, 1 part of emulsifier NP-15 was added to 100g of waste diesel oil and stirred to dissolve, thus obtaining an oil phase. The obtained polyacrylamide solution was then slowly added to the obtained oil phase and stirred and emulsified at a stirring speed of 9000 r / min to obtain a water-in-oil emulsion.

[0216] (2) Preparation of sealing grout:

[0217] The water-in-oil emulsion obtained in step (1) is mixed evenly with other components to obtain a plugging slurry.

[0218] The density of the sealing grout at 25°C was 1.05 g / cm³, as determined by the aforementioned method. 3 The obtained sealing grout was injected into 90°C water. The grout gelled in 20 seconds and fully cured in 75 minutes. Using a testing device, the formed gel was flushed with water, and its mass retention rate was calculated to be 95.5%. After the gel fully cured to form the sealing material, its compressive strength was tested to be 7 MPa, its lap shear strength to be 0.12 MPa, and its compressive strength to be 19.8 MPa.

[0219] Example 9

[0220] Prepare the sealing slurry according to the formulation of the sealing composition in Example 9 of Table 2.

[0221] (1) Preparation of water-in-oil emulsion:

[0222] First, 2 parts of anionic polyacrylamide with a weight average molecular weight of 8 million g / mol were added to 60 parts of water and stirred to dissolve, thus obtaining a polyacrylamide solution. Then, 4 parts of emulsifier OP-15 were added to 100g of waste edible oil and stirred to dissolve, thus obtaining an oil phase. The obtained polyacrylamide solution was then slowly added to the obtained oil phase, and the mixture was stirred and emulsified at a stirring speed of 12000 r / min to obtain a water-in-oil emulsion.

[0223] (2) Preparation of sealing grout:

[0224] The water-in-oil emulsion obtained in step (1) is mixed evenly with other components to obtain a plugging slurry.

[0225] The density of the sealing grout at 25°C was 1.36 g / cm³, as determined by the aforementioned method. 3The obtained sealing grout was injected into water at 140℃. The grout gelled in 10 seconds and fully cured in 39 minutes. Using a testing device, the formed gel was flushed with water, and its mass retention rate was calculated to be 93.1%. After the gel fully cured to form the sealing material, its compressive strength was tested to be 7 MPa, its lap shear strength to be 0.12 MPa, and its compressive strength to be 16.8 MPa.

[0226] Example 10

[0227] Prepare the sealing slurry according to the formulation of the sealing composition in Example 10 of Table 2.

[0228] (1) Preparation of water-in-oil emulsion:

[0229] First, 1 part of anionic polyacrylamide with a weight average molecular weight of 4.5 million g / mol was added to 80 parts of water and stirred to dissolve, thus obtaining a polyacrylamide solution. 0.1 part of emulsifier S-80 was added to 100g of waste engine oil and stirred to dissolve, thus obtaining an oil phase. Then, the obtained polyacrylamide solution was slowly added to the obtained oil phase, and the mixture was stirred and emulsified at a stirring speed of 10,000 r / min to obtain a water-in-oil emulsion.

[0230] (2) Preparation of sealing grout:

[0231] The water-in-oil emulsion obtained in step (1) is mixed evenly with other components to obtain a plugging slurry.

[0232] The density of the sealing grout at 25°C was 1.23 g / cm³, as determined by the aforementioned method. 3 The obtained sealing grout was injected into water at 100℃. The grout gelled in 40 seconds and fully cured in 35 minutes. Using a testing device, the formed gel was flushed with water, and its mass retention rate was calculated to be 97.8%. After the gel fully cured to form the sealing material, its compressive strength was tested to be 7 MPa, its lap shear strength to be 0.11 MPa, and its compressive strength to be 17.5 MPa.

[0233] Example 11

[0234] Prepare the sealing slurry according to the formulation of the sealing composition in Example 11 of Table 2.

[0235] (1) Preparation of water-in-oil emulsion:

[0236] First, 10 parts of anionic polyacrylamide with a weight average molecular weight of 6 million g / mol were added to 70 parts of water and stirred to dissolve, thus obtaining a polyacrylamide solution. Then, 5 parts of emulsifier T-20 were added to 100g of waste edible oil and stirred to dissolve, thus obtaining an oil phase. The obtained polyacrylamide solution was then slowly added to the obtained oil phase and stirred and emulsified at a stirring speed of 9000 r / min to obtain a water-in-oil emulsion.

[0237] (2) Preparation of sealing grout:

[0238] The water-in-oil emulsion obtained in step (1) is mixed evenly with other components to obtain a plugging slurry.

[0239] The density of the sealing grout at 25°C was 1.78 g / cm³, as determined by the aforementioned method. 3 The obtained sealing grout was injected into water at 110℃, where gel formation took 25 seconds and complete curing took 38 minutes. Using a testing device, the formed gel was flushed with water, and its mass retention rate was calculated to be 97%. After the gel completely cured to form the sealing material, its compressive strength was tested to be 7 MPa, its lap shear strength to be 0.14 MPa, and its compressive strength to be 17 MPa.

[0240] Example 12

[0241] The sealing slurry was prepared according to the method of Example 7, and the sealing slurry was prepared according to the formula of the sealing composition in Example 7 in Table 2, except that no silicone crosslinking agent was added.

[0242] The density of the sealing grout at 25°C was 1.05 g / cm³, as determined by the aforementioned method. 3 The obtained sealing grout was injected into water at 60°C. The grout gelled in 45 seconds and fully cured in 40 minutes. Using a testing device, the formed gel was flushed with water, and its mass retention rate was calculated to be 93%. After the gel fully cured to form the sealing material, its compressive strength was tested to be 6.5 MPa, its lap shear strength to be 0.1 MPa, and its compressive strength to be 15.6 MPa.

[0243] Comparative Example 2

[0244] The sealing slurry was prepared according to the method in Example 7, except that polyacrylamide was not added to the water-in-oil emulsion.

[0245] Tests showed that the plugging grout in this comparative example could not form a gel.

[0246] Table 2

[0247]

[0248]

[0249] Example 13

[0250] Step 1: Preparation of water-insoluble material: Mix 20g of salt-resistant polymer SMPFL-C with 2g of polyacrylamide with a weight average molecular weight of 5 million g / mol to obtain water-insoluble material.

[0251] Step 2: Preparation of crosslinking agent: Mix 100g water glass, 100g zirconium citrate and 5g polyethyleneimine, then add 90g water and 0.2g sodium dodecylbenzenesulfonate, and stir evenly at 65℃ to obtain the crosslinking agent;

[0252] Step 3: Mix 100g of water, 150g of chemically solidified material SMHD-1, 12g of water-insoluble material obtained in Step 1, 1g of crosslinking agent obtained in Step 2, and 1g of 2-acrylamide-2-methylpropanesulfonic acid polymer evenly to obtain the plugging slurry.

[0253] The density of the sealing grout at 25°C was 1.65 g / cm³, as determined by the aforementioned method. 3 Under sealed conditions at 90℃, the gel formation time of the sealing grout was 30 minutes, and the complete curing time was 5.5 hours. Using a testing device, the formed gel was flushed with water, and its mass retention rate was calculated to be 95.2%. After the gel completely cured to form the sealing material, its compressive strength was tested to be 7 MPa, its lap shear strength was 0.14 MPa, and its compressive strength was 21.4 MPa.

[0254] Example 14

[0255] Step 1: Preparation of water-insoluble material: Mix 10g of salt-resistant polymer SMVIS-1 with 2g of polyacrylamide with a weight average molecular weight of 10 million g / mol to obtain water-insoluble material.

[0256] Step 2: Preparation of crosslinking agent: Mix 100g of tetraethyl orthosilicate, 80g of zirconium citrate and 7g of polyethyleneimine, then add 60g of water and 0.5g of sodium dodecylbenzenesulfonate, and stir evenly at 40℃ to obtain the crosslinking agent;

[0257] Step 3: Mix 100g of water, 200g of chemically solidifying material SMHD-1, 12g of water-dispersible material obtained in Step 1, 3g of crosslinking agent obtained in Step 2, 4g of hydroxycarboxylic acid polymer and 20g of cenospheres evenly to obtain the sealing slurry.

[0258] The density of the sealing grout at 25°C was 1.72 g / cm³, as determined by the aforementioned method. 3Under sealed conditions at 120℃, the sealing grout gelled in 20 minutes and fully cured in 4.5 hours. Using a testing device, the formed gel was flushed with water, and its mass retention rate was calculated to be 94.8%. After the gel fully cured to form the sealing material, its compressive strength reached 7 MPa, its lap shear strength was 0.13 MPa, and its compressive strength was 23.8 MPa.

[0259] Example 15

[0260] Step 1: Preparation of water-indispersible material: 20g of salt-resistant polymer SMHV-C and 4g of nonionic polyacrylamide with a weight-average molecular weight of 14 million g / mol were mixed evenly to obtain water-indispersible material;

[0261] Step 2: Preparation of crosslinking agent: Mix 100g of KH560, 150g of chromium lactate and 3g of polyethyleneimine, then add 50g of water and 1g of sodium dodecylbenzenesulfonate, and stir evenly at 50℃ to obtain the crosslinking agent;

[0262] Step 3: Mix 100g of water, 180g of chemically solidified material SMHD-2, 15g of water-insoluble material obtained in Step 1, 2.5g of crosslinking agent obtained in Step 2, 3.5g of hydroxycarboxylic acid polymer and 30g of barite evenly to obtain the sealing slurry.

[0263] The density of the sealing grout at 25°C was 1.69 g / cm³, as determined by the aforementioned method. 3 Under sealed conditions at 150℃, the sealing grout gelled in 20 minutes and fully cured in 3.2 hours. Using a testing device, the formed gel was flushed with water, and its mass retention rate was calculated to be 93.7%. After the gel fully cured to form the sealing material, its compressive strength reached 7 MPa, its lap shear strength was 0.12 MPa, and its compressive strength was 22.7 MPa.

[0264] Example 16

[0265] The sealing slurry was prepared according to the method of Example 13, except that in step 3, 100g of water, 50g of chemically solidified material SMHD-1, 10g of water-insoluble material and 0.1g of crosslinking agent were stirred evenly to obtain the sealing slurry.

[0266] The density of the sealing grout at 25°C was 1.5 g / cm³, as determined by the aforementioned method. 3Under sealed conditions at 80℃, the sealing grout gelled in 40 minutes and fully cured in 6 hours. Using a testing device, the formed gel was flushed with water, and its mass retention rate was calculated to be 91.3%. After the gel fully cured to form the sealing material, its compressive strength was tested to be 7 MPa, its lap shear strength to be 0.10 MPa, and its compressive strength to be 17.5 MPa.

[0267] Example 17

[0268] The solidified plugging grout was prepared according to the method of Example 13, except that in step 1, 20g of SMPFL-C and 6g of polyacrylamide with a weight average molecular weight of 5 million g / mol were mixed evenly to obtain a water-insoluble material; in step 2, 100g of water glass, 10g of zirconium citrate and 10g of polyethyleneimine were mixed, and then 90g of water and 0.2g of sodium dodecylbenzenesulfonate were added and stirred evenly at 65°C to obtain a crosslinking agent.

[0269] The density of the sealing grout at 25°C was 1.65 g / cm³, as determined by the aforementioned method. 3 Under sealed conditions at 100℃, the gel formation time of the sealing grout was 25 minutes, and the complete curing time was 5 hours. Using a testing device, the formed gel was flushed with water, and its mass retention rate was calculated to be 94.1%. After the gel completely cured to form the sealing material, its compressive strength was tested to be 7 MPa, its lap shear strength was 0.11 MPa, and its compressive strength was 20.4 MPa.

[0270] Example 18

[0271] The consolidation and plugging grout was prepared according to the method of Example 13, except that 100g of water glass was not added in step 2. That is, step 2: preparation of crosslinking agent: 100g of zirconium citrate and 5g of polyethyleneimine were mixed, and then 90g of water and 0.2g of sodium dodecylbenzenesulfonate were added. The mixture was stirred evenly at 65°C to obtain the crosslinking agent.

[0272] The density of the sealing grout at 25°C was 1.65 g / cm³, as determined by the aforementioned method. 3 Under sealed conditions at 90℃, the gel formation time of the sealing grout was 30 minutes, and the complete curing time was 5.3 hours. Using a testing device, the formed gel was flushed with water, and its mass retention rate was calculated to be 92.3%. After the gel completely cured to form the sealing material, its compressive strength was tested to be 7 MPa, its lap shear strength was 0.11 MPa, and its compressive strength was 19.5 MPa.

[0273] Example 19

[0274] The consolidation and plugging grout was prepared according to the method in Example 13, except that the testing conditions were changed from a 90°C sealed condition to a 180°C sealed condition, as detailed below:

[0275] The density of the sealing grout at 25°C was 1.65 g / cm³, as determined by the aforementioned method. 3 Under sealed conditions at 180℃, the sealing grout gelled in 10 minutes and fully cured in 0.5 hours. Using a testing device, the formed gel was flushed with water, and its mass retention rate was calculated to be 96.5%. After the gel fully cured to form the sealing material, its compressive strength was tested to be 7 MPa, its lap shear strength to be 0.12 MPa, and its compressive strength to be 18.9 MPa.

[0276] Comparative Example 3

[0277] The sealing slurry was prepared according to the method of Example 13, except that no chemical binder SMHD-1 was added in step 3, i.e., the amount of chemical binder SMHD-1 was 0. Under the flushing of water, the gel formed by this sealing slurry could not solidify to form a plug and could not achieve the effect of sealing and bearing pressure.

[0278] Comparative Example 4

[0279] The sealing slurry was prepared according to the method of Example 13, except that step 1 was not included, and no water-insoluble material was added in step 3, i.e., the water-insoluble material content was 0%. The gel formed by this sealing slurry is easily diluted by water and is easily washed away by flowing water. It also cannot solidify to form a plug and therefore cannot achieve the effect of sealing leaks and bearing pressure.

[0280] As can be seen from Examples 1-19, the gel formed by the sealing slurry prepared using the sealing composition of the present invention has anti-water dilution properties. After entering the flowing water layer, it can remain in the flowing water-containing leakage layer and solidify after a period of time under the temperature and pressure environment of the formation, forming a solidified material with high compressive strength. The compressive strength of this solidified material is above 16 MPa, the mass retention rate is above 90%, and the pressure bearing capacity can reach 7 MPa. Thus, it solves the leakage problem in formations containing flowing water.

[0281] As can be seen from the results of the above embodiments and comparative examples, the embodiments of the present invention have significant advantages in terms of resistance to water erosion and high temperature resistance. When applied to water-bearing formations, they have higher mass retention rate and compressive strength. They can be applied to water-bearing formations with temperatures not exceeding 180°C, especially water-bearing formations.

[0282] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A method for plugging leaks in oil wells, characterized in that, The method includes: The plugging composition is injected into the formation fracture of the oil well so that the plugging composition cross-links and forms a gel during the injection process, or the plugging composition is cross-linked and forms a gel before being injected into the formation fracture of the oil well. Under formation conditions, the gel undergoes secondary cross-linking at the lost formation and solidifies to form a plugging material. The gel retains over 90% of its mass after being flushed with water at a flow rate of 10 m / min for 30 minutes at 50-180℃; the overlap shear strength of the sealing material is 0.1-0.14 MPa; and the leaking formation is a formation containing flowing water. The plugging composition comprises the following components: a crosslinkable polymer, a crosslinking agent, a reinforcing agent I, and a solvent; wherein the crosslinking agent contains an organometallic crosslinking agent, an allyl crosslinking agent, and a silicone crosslinking agent, and the mass ratio of the allyl crosslinking agent, the metal crosslinking agent, and the silicone crosslinking agent is 1:0.3-8:0.1-12; the organometallic crosslinking agent is selected from at least one of organozirconium crosslinking agents, organochromium crosslinking agents, and organoaluminum crosslinking agents. The reinforcing agent I comprises the monomer shown in formula (I), dopamine, and an initiator; Equation (I) Among them, R1, R2, R 21 and R 22 Each is independently hydrogen or C1-C 10 Straight-chain or branched alkyl groups; The crosslinkable polymer exists in the form of a water-in-oil emulsion, which comprises the crosslinkable polymer, oil, water, and an emulsifier. The weight parts of each component in the plugging composition are as follows: 100 parts of water-in-oil emulsion, 0.01-8 parts of crosslinking agent, 3-30 parts of the monomer shown in formula (I), 0.01-2 parts of dopamine, and 0.01-8 parts of initiator. The mass ratio of the crosslinkable polymer, oil, water, and emulsifier is 0.5-15:100:50-100:0.05-10. The crosslinkable polymer is anionic polyacrylamide, and the weight-average molecular weight of the anionic polyacrylamide is 2.5-10 million g / mol.

2. The method according to claim 1, wherein, The pressure resistance of the sealing material is not less than 7 MPa.

3. The method according to claim 1 or 2, wherein, The compressive strength of the sealing material is not less than 16 MPa.

4. The method according to claim 3, wherein, The compressive strength of the sealing material is 18-25 MPa.

5. The method according to claim 1 or 2, wherein, The temperature of the lost formation is 50-180℃.

6. The method according to claim 1, wherein, The oil is selected from at least one of waste white oil, waste diesel oil, waste engine oil, and waste edible oil. And / or, the emulsifier is selected from at least one of octylphenol polyoxyethylene ether-10, octylphenol polyoxyethylene ether-15, nonylphenol polyoxyethylene ether-10, nonylphenol polyoxyethylene ether-15, Tween-20, Tween-60, Span-80, Span-85 and sodium dodecylbenzenesulfonate.

7. The method according to claim 1, wherein, The mass ratio of the crosslinkable polymer, oil, water, and emulsifier is 1-10:100:60-90:0.1-5; And / or, the weight-average molecular weight of the anionic polyacrylamide is 3-8 million g / mol.

8. The method according to claim 1, wherein, The reinforcing agent I further includes at least one of the monomers shown in formula (II), formula (III), formula (IV), formula (V), and formula (VI): Equation (II), Equation (III), Formula (IV), Equation (V), Formula (VI), Among them, R3, R4, R6, R7, R 11 R 12 R 13 R 14 R 15 R 16 R 18 R 19 and R 20 Each is independently hydrogen or C1-C 10 Straight-chain or branched alkyl groups; R5 and R 17 Each independently is C1-C 20 Straight-chain or branched alkylene groups; R8, R9 and R 10 One of them is C1-C 20 The chain consists of a straight-chain or branched alkyl group, with the other two being hydrogen or C1-C2 respectively. 10 Straight-chain or branched alkyl groups; R' is C1-C 10 The straight-chain or branched alkylene groups; M1 and M2 are each independently H, Na, Li or K; x is any integer from 4 to 20, and n is any integer from 3 to 10.

9. The method according to claim 8, wherein, Based on 100 parts by weight of water-in-oil emulsion, the monomer shown in formula (II) is 0.2-20 parts by weight; And / or, based on 100 parts by weight of water-in-oil emulsion, the monomer shown in formula (III) is 0.5-20 parts by weight; And / or, based on 100 parts by weight of water-in-oil emulsion, the monomer shown in formula (IV) is 0.2-5 parts by weight; And / or, based on 100 parts by weight of water-in-oil emulsion, the monomer shown in formula (V) is 0.5-20 parts by weight; And / or, based on 100 parts by weight of water-in-oil emulsion, the monomer shown in formula (VI) is 0.5-10 parts by weight.

10. The method according to claim 9, wherein, Based on 100 parts by weight of water, the monomer shown in formula (II) is 2-15 parts by weight. And / or, based on 100 parts by weight of water, the monomer shown in formula (III) is 1-15 parts by weight. And / or, based on 100 parts by weight of water, the monomer shown in formula (IV) is 0.5-4 parts by weight; And / or, based on 100 parts by weight of water, the monomer shown in formula (V) is 1-15 parts by weight. And / or, based on 100 parts by weight of water, the monomer shown in formula (VI) is 1-8 parts by weight.

11. The method according to claim 1, wherein, The allyl crosslinking agent is selected from at least one of N,N'-methylenebisacrylamide, glycerol triacrylate, ethoxylated trimethylolpropane triacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, and ethoxylated pentaerythritol tetraacrylate. And / or, the silicon crosslinking agent is selected from at least one of water glass, ethyl silicate, and γ-methacryloyloxypropyltrimethoxysilane.

12. The method according to claim 1, wherein, The mass ratio of the allyl crosslinking agent, organometallic crosslinking agent, and silicon crosslinking agent is 1:0.5-5:0.2-10.

13. The method according to claim 1 or 2, wherein, The initiator is selected from at least one of potassium persulfate, ammonium persulfate, sodium persulfate, benzoyl peroxide, azobisisobutyramidine hydrochloride, di-tert-butyl peroxide, dodecyl peroxide, azobisisobutyronitrile, and cumene hydroperoxide.

14. The method according to claim 1 or 2, wherein, The density of the plugging composition after mixing is 1-2 g / cm³ at 25°C. 3 .

15. The method according to claim 14, wherein, The density of the sealing composition after mixing is 1.2-1.65 g / cm³ at 25°C. 3 .

Citation Information

Patent Citations

  • Pretreating agent for water-containing stratum leaking stoppage and preparation method and application thereof

    CN111849437A

  • Simulation device for leaking stoppage of water-containing leakage layer

    CN113123756A

  • Plugging agent composition, plugging agent and preparation method and application of the plugging agent

    CN110734754A

  • Composite gel leaking stoppage material and composite gel leaking stoppage slurry

    CN112280543A